1986
DOI: 10.1177/107110078600600504
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Dislocations of the Tarsometatarsal Joints: End Results Correlated with Pathology and Treatment

Abstract: Seventy-two patients with 76 fracture-dislocations of the Lisfranc tarsometatarsal joint complex were evaluated. Fifty-eight (81%) were polytrauma patients and the remainder suffered isolated injuries. Sixty of the original 72 patients were available for long-term study. Eight of these had an amputation at or shortly after the original admission, leaving 52 patients with 55 Lisfranc injuries for analysis. The average length of follow-up was 4.2 years (range, 20 months to 11 years). According to the Painful Foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
432
2
43

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(504 citation statements)
references
References 11 publications
10
432
2
43
Order By: Relevance
“…It has been demonstrated that anatomic reduction and rigid stabilization of the Lisfranc complex is the standard of care for these injuries [27]. Open reduction and internal fixation (ORIF) and primary arthrodesis have both been evaluated as treatment options with acceptable results [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that anatomic reduction and rigid stabilization of the Lisfranc complex is the standard of care for these injuries [27]. Open reduction and internal fixation (ORIF) and primary arthrodesis have both been evaluated as treatment options with acceptable results [18].…”
Section: Introductionmentioning
confidence: 99%
“…[1] We used the Modified Hardcastle Classification [7] for this study (Table 1). Patients were then contacted for further evaluation, and all data were entered in the data collection form.…”
Section: Methodsmentioning
confidence: 99%
“…2,4,12 Most investigators have concluded that there is little place for the nonoperative management of Lisfranc fracture-dislocations when a 2-mm or greater diastasis is found between the bases of the first and second metatarsals and medial and middle cuneiforms, because it is difficult to maintain anatomic reduction by closed reduction and immobilization alone. 1,2,4,5,7,9,14,15 Curtis et al 16 recommend surgical reduction for all athletes and active persons. Surgical reduction as soon as possible after the injury is recommended by most orthopaedic surgeons.…”
Section: Dotted Lines) a 2-mm Diastasis Is Noted Between The Medial mentioning
confidence: 99%
“…12 Closed or open reduction with Kirschner wire (K wire) internal fixation has historically been used for the treatment of these injuries. 14 The use of open reduction and internal fixation with AO screws (meets Arbeitsgemeinschaft fü r Osteosynthesefragen international standards) has grown increasingly popular for Lisfranc fracture-dislocations. 12 After screw fixation, most orthopedists recommend immobilization and non-weight-bearing status for 8 to 12 weeks.…”
Section: Dotted Lines) a 2-mm Diastasis Is Noted Between The Medial mentioning
confidence: 99%